2014
DOI: 10.1515/ijme-2015-0012
|View full text |Cite
|
Sign up to set email alerts
|

Validating Dart Model

Abstract: The primary objective of the study was to quantitatively test the DART model, which despite being one of the most popular representations of co-creation concept was so far studied almost solely with qualitative methods. To this end, the researchers developed a multiple measurement scale and employed it in interviewing managers. The statistical evidence for adequacy of the model was obtained through CFA with AMOS software. The findings suggest that the DART model may not be an accurate representation of co-crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 22 publications
(16 reference statements)
1
21
0
1
Order By: Relevance
“…Specifically, the factors Risk 2 and Transparency explain little variance in its indicators and are too similar to other factors. This finding is consistent with our previous research on DART [Mazur, Zaborek, 2014], where -while using a different sample -it was concluded that the DART framework works better for manufacturing companies, possibly because it was originally developed through a qualitative investigation of several manufacturing firms. Even though services firms are generally worse represented by the model, for factors other than the problematic Risk 2 and Transparency reliability and validity is at least adequate, and Dialog and Risk 1 have their measurement models equivalent to manufacturers' (as indicated by insignificant differences between regression weights).…”
Section: Research Findingssupporting
confidence: 91%
See 2 more Smart Citations
“…Specifically, the factors Risk 2 and Transparency explain little variance in its indicators and are too similar to other factors. This finding is consistent with our previous research on DART [Mazur, Zaborek, 2014], where -while using a different sample -it was concluded that the DART framework works better for manufacturing companies, possibly because it was originally developed through a qualitative investigation of several manufacturing firms. Even though services firms are generally worse represented by the model, for factors other than the problematic Risk 2 and Transparency reliability and validity is at least adequate, and Dialog and Risk 1 have their measurement models equivalent to manufacturers' (as indicated by insignificant differences between regression weights).…”
Section: Research Findingssupporting
confidence: 91%
“…In developing the statements for the scale we were guided by several earlier works, in particular Mazur and Zaborek [2014], Albinsson et al [2011Albinsson et al [ , 2016, Ruso Spena et al [2012], Prahalad and Ramaswamy [2000, 2004a, 2004b, 2004c. Specific reasons for the content of the listed items are discussed below.…”
Section: Tmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, four items for dialogue, three items for access, three items for risk assessment, and three items for transparency were adapted from Albinsson et al (2016). Two items from Mazur and Zaborek (2014) were used, one for risk and one for transparency. For access, one item is adopted from Taghizadeh et al (2016).…”
Section: Measures Developmentmentioning
confidence: 99%
“…Do propagatorów tego podejścia należą m.in. Prahalad i Ramaswamy 22 , którzy zaproponowali model działań przedsiębiorstwa zorientowanego na doświadczenia klientów 23 oraz Vargo i Lusch 24 .…”
Section: Zastosowanie Narzędzi Internetowych W Działaniach Marketingounclassified